Pengaruh Penggunaan Media Elektronika Terhadap Motivasi Belajar Pendidikan Agama Kristen Siswa Kelas IX Di SMP Negeri 1 Sipoholon Tahun Pembelajaran 2023/2024 - Ruben Sitinjak (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
The research aims to determine the effect of using electronic media on the learning motivation of PAK class IX students at SMP Negeri 1 Sipoholon for the 2023/2024 academic year. The research hypothesis is that there is a positive and significant influence between the use of electronic media on the learning motivation of PAK class IX students at SMP Negeri 1 Sipoholon for the 2023/2024 academic year. This research is a regression research using the Quantitative Inferential Method.The population of all class IX students at SMP Negeri 1 Sipoholon for the 2023/2024 academic year is 190 people. Random sampling (random sampling) was 30% of the total population, namely 57 people. The research instrument is a closed questionnaire.The results of the analysis requirements obtained a value of rxy=0.678>rtabel=0.226 and tcount=6.840>ttable=2.000 indicating a relationship between the use of electronic media and students' PAK learning motivation and obtained a regression equation . Hypothesis testing obtained Fcount=46.542>Ftable=1.39 so H0 is rejected and Ha is accepted. The research concluded that there was a positive and significant influence between the use of electronic media on the learning motivation of PAK class IX students at SMP Negeri 1 Sipoholon for the 2023/2024 academic year, amounting to 45.97%.